2007
DOI: 10.1152/ajpendo.00477.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of the autonomic nervous system in the development of hyperinsulinemia by high-carbohydrate formula feeding to neonatal rats

Abstract: Mitrani P, Srinivasan M, Dodds C, Patel MS. Role of the autonomic nervous system in the development of hyperinsulinemia by high-carbohydrate formula feeding to neonatal rats. Am J Physiol Endocrinol Metab 292: E1069 -E1078, 2007. First published December 12, 2006 doi:10.1152/ajpendo.00477.2006.-An early dietary intervention in the form of a high-carbohydrate (HC) milk formula in neonatal rat pups results in immediate onset of hyperinsulinemia. While increased insulin secretion in HC rats has been shown to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The metabolic phenotype (body weight, serum hormone levels, insulin secretory capacity of islets, and hypothalamic characteristics) of the HF rats during both the preweaning and postweaning periods was similar to that of the MF rats, which suggests that the development of the HC phenotype was not influenced by the artificial rearing technique employed in our studies (11,16,18,19,30,33,34). Because of the similarity in the phenotype of MF and HF rats, we used only MF rats as control in the present study.…”
Section: Methodsmentioning
confidence: 53%
See 2 more Smart Citations
“…The metabolic phenotype (body weight, serum hormone levels, insulin secretory capacity of islets, and hypothalamic characteristics) of the HF rats during both the preweaning and postweaning periods was similar to that of the MF rats, which suggests that the development of the HC phenotype was not influenced by the artificial rearing technique employed in our studies (11,16,18,19,30,33,34). Because of the similarity in the phenotype of MF and HF rats, we used only MF rats as control in the present study.…”
Section: Methodsmentioning
confidence: 53%
“…Although insulin secretion is regulated primarily by circulating glucose concentrations (15), the ANS also controls insulin secretion by islets (2,32). HC islets demonstrated aberrations at both of these levels of regulation of insulin secretion: 1) a leftward shift in the response to glucose (1,29) and 2) an increased PNS activity (increased response to ACh stimulation) and a compromised SNS activity (diminished inhibition by OM) (18,19). Our results indicate that although serum insulin levels were normalized in the adult HC/PF rats, the in vitro insulin secretory capacity of HC/PF islets did not differ from that observed for HC islets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to an altered sensitivity to glucose, the immediate onset of hyperinsulinaemia and its persistence throughout the period of the HC dietary modification was supported by an increase in the parasympathetic input and decrease in the sympathetic input (Mitrani et al 2007a). In normal rats, islet b-cell glucose-induced insulin secretion is stimulated by acetylcholine binding to muscarinic type 3 receptors, and inhibited by a 2 -adrenergic receptor catecholamine binding.…”
Section: Effects Observed During the Period Of Hc Dietary Modificationmentioning
confidence: 99%
“…Previous in vitro studies of insulin secretion have found that islets isolated from 12-day-old HC rats treated with ACh and GLP-1 resulted in greater increases in GSIS compared with MF islets, suggesting increased ␤-cell responsiveness to cholinergic and incretin stimulation during the neonatal period in HC rats (46,47). Furthermore, evidence in 12-day-old HC rats showed that altered autonomic activity is involved in the immediate onset of hyperinsulinemia in response to the HC dietary intervention (31).…”
Section: Parasympathetic-stimulated Insulin Secretion In 100-day-old mentioning
confidence: 99%